Halal Certification for Financial Products: A Transaction Cost Perspective - Raphie Hayat; Frank A.G. den Butter; Udo Kock (Tinbergen Institute, 2011)
Halal certification of financials product may reduce transaction costs for its buyers when it provides a trusted standard for investors that seek to comply with Islamic law. However, we show that in practice it takes considerable amounts of time (20 days ) and money (USD 122,000) to obtain a halal certification. Mainly, this is because the market is very concentrated and forms a closed circuit. About 20 Sharia scholars control more than half the market, of which the top 3 earn an estimated USD 4.5 mln in fees per year. Moreover this market seems plagued by a number of problems, most notably a strong incentive to be excessively lenient in certification, sub-standard governance practices, lack of consensus regarding certification standards and limited knowledge of finance. Therefore it is questionable whether the reduction in transaction costs through halal certification outweighs the costs of certification. Consolidation of the numerous ways halal certifica tion can be obtained and moving halal certification more into the public goods sphere, where a neutral non-profit government induced party should assume the current role of the halal certifiers, may enhance the reputation of certifies and reduce the transaction costs associated with halal certification.
urn:NBN:nl:ui:31-1871/38562
Keywords: L14; L15; D23; D82; 330; Islamic finance; quality certification; certifier behaviour; transaction costs; information asymmetries; credence goods